Big Data Innovation and Its Influence on Strategic Accounting and Business Performance - Ali Hasheem (PT. BATARI EDU CALYA, 2024)
The integration of big data analytics into strategic management accounting represents a transformative paradigm shift in contemporary business operations, particularly within emerging economies such as Tanzania. This study investigates the influence of big data innovation on strategic accounting practices and business performance within the Tanzanian context. Employing a quantitative research methodology with Partial Least Squares Structural Equation Modeling (PLS-SEM), this research examines the relationships between big data analytics capabilities, strategic management accounting practices, and organizational performance outcomes. The findings reveal that big data analytics significantly enhances management accounting information systems, facilitating improved decision-making processes and strategic planning capabilities. Furthermore, the study demonstrates that innovation culture mediates the relationship between knowledge-based dynamic capabilities and innovation performance in Tanzanian enterprises. The results indicate that while large volumes of data are not necessarily superior, the strategic application of data analytics serves as a pertinent determinant of firm innovation and market competitiveness. This research contributes to the theoretical understanding of digital transformation in accounting practices within developing economies and provides practical implications for Tanzanian businesses seeking to leverage big data for enhanced strategic performance.